A sock for foot-drop: A preliminary study on two chronic stroke patients. (October 2014) - Prenton, Sarah; Kenney, Laurence PJ; Cooper, Glen; Major, Matthew J
Background: Foot-drop is a common motor impairment of chronic stroke patients, which may be addressed with an ankle foot orthosis. Although there is reasonable evidence of effectiveness for ankle foot orthoses, user compliance is sometimes poor. This study investigated a new alternative to the ankle foot orthosis, the dorsiflex sock. Case description and methods: The dorsiflex sock was evaluated using an A-B single case experimental design. Two community-dwelling, chronic stroke patients with foot-drop participated in this study. Measures were selected to span the International Classification of Function, Disability and Health domains and user views on the dorsiflex sock were also collected. Findings and outcomes: The dorsiflex sock was not effective in improving participants' walking symmetry, speed or energy expenditure. Participant 1 showed improvement in the distance he could walk in 6 min when using the dorsiflex sock, but this was in keeping with a general improvement trend over the course of this study. However, both participants viewed the dorsiflex sock positively and reported a positive effect on their walking. Conclusion: Despite positive user perceptions, the study found no clear evidence that dorsiflex sock is effective in improving foot-drop. Clinical relevance: Although the dorsiflex sock offers an attractive alternative to an ankle foot orthosis, the case studies found no clear evidence of its efficacy. Clinicians should view this device with caution until further research becomes available.